ANALISIS DISCLOSURE PERANAN JAMINAN TERHADAP PEMAKAIAN JASA KREDIT PADA PT PEGADAIAN SYARIAH - Ustman, Ustman; Sekartaji, Wilis indah (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
This study aims to determine the role disclosure of the guarantee on the use of credit services PT Pegadaian Syariah. This research was carried out PT Pegadaian Syariah cabang Pamekasan. This method of research is descriptive qualitative with the type of qualitative data. The informants used were the employees of the pawnshop and the pawnshop customer. Data collection techniques used in the form of observation data, interviews, and documentation. From the results of the analysis obtained is the disclosure of the role of collateral greatly affect the size of the credit service, which amount is determined from the collateral that has been assessed. But PT Pegadaian Syariah has not fully run Ar-Rahn in sharia, the disclosue of this guarantee role is the spearhead in running the pawn business. PT Pegadaian Syariah makes a guarantee to assess the loan funds to be disbursed, regardless of the function of the guarantee in Islam. PT Pegadaian Syariah does not provide an ijarah (save deposit box) to the customer, to withdraw the administrative fee / as the cost of goods deposit.